Reflection of tectonic structures of platform cover of the North of Russian plate in atmospheric field, character of geomagnetic variations and deep’s decontamination - Kutinov, Y.; Chistova, Z. (Геофизический журнал, 2010)
Researches is executed at financial support RFBR, the grant 08-05-99816 “Active processes in the environment, their monitoring and forecasting in the territory of Arkhangelsk region” and Programs DSE of the Russian Academy of Science N 9 " Geospheres interactions", Project “Studies process of interaction geospheres in active geological structure in the North of Russian Plate”.